2016
DOI: 10.18632/oncotarget.13021
|View full text |Cite
|
Sign up to set email alerts
|

Notch1—WISP-1 axis determines the regulatory role of mesenchymal stem cell-derived stromal fibroblasts in melanoma metastasis

Abstract: Mesenchymal stem cells-derived fibroblasts (MSC-DF) constitute a significant portion of stromal fibroblasts in the tumor microenvironment (TME) and are key modulators of tumor progression. However, the molecular mechanisms that determine their tumor-regulatory function are poorly understood. Here, we uncover the Notch1 pathway as a molecular determinant that selectively controls the regulatory role of MSC-DF in melanoma metastasis. We demonstrate that the Notch1 pathway's activity is inversely correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…3A). Consistently, MSC-DF Notch1−/− robustly increased lung metastasis [33]. These results indicate that turning "OFF" Notch1 signaling in MSC-DF promotes melanoma invasion and metastasis whereas turning "ON" Notch1 signaling in MSC-DF suppresses melanoma invasion and metastasis.…”
Section: The Intracellular Notch1 Signaling Determines Capability Of supporting
confidence: 56%
“…3A). Consistently, MSC-DF Notch1−/− robustly increased lung metastasis [33]. These results indicate that turning "OFF" Notch1 signaling in MSC-DF promotes melanoma invasion and metastasis whereas turning "ON" Notch1 signaling in MSC-DF suppresses melanoma invasion and metastasis.…”
Section: The Intracellular Notch1 Signaling Determines Capability Of supporting
confidence: 56%
“…Control, control group; negative, negative control group; miR-138 mimics, miR-138 overexpression group; anti-PI3K, PI3K inhibitor (LY294002) and miR-138 overexpression group. biotherapy, radiotherapy and/or chemotherapy, although these methods have to date yielded unsatisfactory clinical effects on the prognosis and mortality rate of patients (21). In the present study the results revealed that miR-138 expression was significantly downregulated in patients with MM and the MM cell line A2058 when compared with normal controls.…”
Section: Discussionsupporting
confidence: 41%
“…In this context, adjacent differentiated keratinocytes or endothelial cells are responsible for the cell surface Notch ligands, and neither Notch ligands nor active Notch signaling are detected in the stromal fibroblasts (70,71). Interestingly, when constitutively active Notch signaling was ectopically engineered into fibroblast cells by overexpressing a NOTCH1 intracellular domain (N IC ), WISP1 expression was elevated through increased transcription, suggesting that WISP1 is a downstream target of Notch signaling (50,51). Using engineered primary human dermal fibroblasts, Shao et al (50) showed in vivo, complemented by in vitro studies using conditioned media, that these cells repressed melanoma growth and angiogenesis but showed no effect on tumor migration.…”
Section: Wisp1 Stimulates Melanoma Invasion and Metastasismentioning
confidence: 99%